ANALISIS EFEKTIVITAS SISTEM INFORMASI ANJUNGAN DALAM PELAYANAN JASA BONGKAR MUAT PT PELABUHAN INDONESIA III (PERSERO) REGIONAL JAWA TIMUR - ningsih, dwi muji; nurhadi, nurhadi (Jurnal Bisnis Indonesia, 2019)
Implementation of information systems in the enterprise need to be evaluated to measure the success rate of the system. Judging from the degree of use, user satisfaction, as well as the impact of the use of the system for individual/company. This study aims to measure the effect of system quality, information quality, and service quality over the use and satisfaction of individual users as well as the impact of the use of the Anjungan in the loading and unloading services PT Pelindo III Regional East Java. The study population was the Anjungan and terminal customers Jamrud. Samples were obtained using purposive sampling technique amounted to 58 companies. Data were collected by questionnaire. The data collected using the Partial Least Square. The results show that the Quality System and significant positive effect on the Use and User Satisfaction. Information quality and no significant positive effect on usage, and no significant negative effect on User Satisfaction. Quality of Service positive and significant impact on usage, and no significant negative effect on User Satisfaction. The use of positive and not significant to user satisfaction. The use of a significant negative effect on the impact of the individual. User satisfaction and no significant negative effect on the impact of the individual.   Keywords: System quality, information quality, service quality, and usage, user satisfaction, individual impact.